Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1055/s-0037-1612818
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative thrombocytopenia may predict poor surgical outcome after extended hepatectomy

Abstract: Background. It is a novel idea that platelet counts may be associated with postoperative outcome following liver surgery. This may help in planning an extended hepatectomy (EH), which is a surgical procedure with high morbidity and mortality. Aim. The aim of this study was to evaluate the predictive potential of platelet counts on the outcome of EH in patients without portal hypertension, splenomegaly, or cirrhosis. Methods. A series of 213 consecutive patients underwent EH (resection of ≥ five liver segments)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The PLT was significantly lower in patients with PHLF in one of these studies; no significant correlation between PLT and PHLF was observed in the other two. Of the remaining 13 studies (5260 patients), seven used a cut‐off PLT of 100/nl and five a cut‐off value of 150/nl. Venkat and colleagues reported outcomes for both PLT cut‐off values.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The PLT was significantly lower in patients with PHLF in one of these studies; no significant correlation between PLT and PHLF was observed in the other two. Of the remaining 13 studies (5260 patients), seven used a cut‐off PLT of 100/nl and five a cut‐off value of 150/nl. Venkat and colleagues reported outcomes for both PLT cut‐off values.…”
Section: Resultsmentioning
confidence: 88%
“…Alkozai and colleagues, Reidiger et al . and Ratti and co‐workers reported only patients with liver metastasis, whereas all primary, metastatic and benign tumours were indications for hepatectomy in five studies . PHLF rates ranged from 0 per cent to 43·1 per cent, and mortality rates from 0·5 per cent to 15·6 per cent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations